Vascular Choroidal Alterations in Uncomplicated Third-Trimester Pregnancy - Jan A. M. Sochurek; Michael Gembicki; Salvatore Grisanti; Mahdy Ranjbar (Tomography, 2022)
(1) Purpose: To evaluate the anatomy and perfusion of choroidal substructures in third-trimester pregnant women using optical coherence tomography (OCT) and OCT angiography (OCTA) imaging. (2) Methods: In this cross-sectional study, women in their third trimester of uncomplicated pregnancy and non-pregnant age-matched women were recruited. Participants underwent enhanced depth imaging (EDI) OCT and OCTA. Subfoveal choroidal thickness (SFCT), as well as choroidal sublayer perfusion, were compared between groups. (3) Results: In total, 26 eyes of 26 pregnant and 26 eyes of 26 non-pregnant women were included. The median age in both groups was 29 years. The median SFCT was 332 (211–469) µm in the pregnant group and 371.5 (224–466) µm in the non-pregnant cohort (p = 0.018). The median choriocapillaris perfusion (CCP) was significantly lower in the pregnant group (46% vs. 48%, p = 0.039). Moreover, Haller’s layer perfusion correlated significantly with mean arterial pressure in non-pregnant women (CC = 0.430, p = 0.028) but not in pregnant ones (CC = 0.054, p = 0.792). (4) Conclusions: SFCT was found to be thinner and CCP was lower in third-trimester pregnant women. Hormonal changes during pregnancy and consecutive impacts on autoregulation of small choroidal vessels might play an important role. Therefore, altered choroidal measurements during third-trimester pregnancy should be carefully evaluated as, to some extent, it could be a normal physiological change.